2015
DOI: 10.1007/s12603-015-0463-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum long-chain omega-3 polyunsaturated fatty acids and future blood pressure in an ageing population

Abstract: Higher serum long-chain omega-3 PUFA concentration, a biomarker of fish or fish oil consumption, may not have an impact on future blood pressure in an ageing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The authors suggested that the vitamin D-induced increase in calcium absorption could promote vascular calcification, which in turn could lead to increased arterial stiffness and greater hypertension risk. In the current study, vitamin D supplementation did not impact on the measured resting arterial blood flow parameters, however, in the current study this was a short duration supplementation that may not have resulted in comparable increases in circulating concentrations of 1,25-dihydroxyvitamin D. The lack of impact of EPA supplementation on the measured resting arterial blood flow parameters in the current study, concurs with recent findings, that higher serum biomarkers of ω-3 consumption, may not impact on future blood pressure ( 43 ).
Table 2 Changes in blood kinetic parameters in response to immobilisation and supplementation
…”
Section: Discussionsupporting
confidence: 87%
“…The authors suggested that the vitamin D-induced increase in calcium absorption could promote vascular calcification, which in turn could lead to increased arterial stiffness and greater hypertension risk. In the current study, vitamin D supplementation did not impact on the measured resting arterial blood flow parameters, however, in the current study this was a short duration supplementation that may not have resulted in comparable increases in circulating concentrations of 1,25-dihydroxyvitamin D. The lack of impact of EPA supplementation on the measured resting arterial blood flow parameters in the current study, concurs with recent findings, that higher serum biomarkers of ω-3 consumption, may not impact on future blood pressure ( 43 ).
Table 2 Changes in blood kinetic parameters in response to immobilisation and supplementation
…”
Section: Discussionsupporting
confidence: 87%
“…In most previous studies, selenium's harmful effect on hypertension was more likely to be seen in selenium-replete populations and protective effect seen in selenium-deplete populations [18]. Moreover, the definition of hypertension varied among different countries, such as Belgium [8], Denmark [11], Finland [26 ], and the United States [17]. Other factors contributing to the inconsistent results include differences in study design, adjustment for confounding factors and the difference in the age range covered by a study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, elevated childhood BP has been shown to predict elevated BP in adolescence and adulthood [57] and other adulthood cardiovascular diseases [810]. Serum and erythrocyte fatty acids (FA) have been suggested to be associated with BP in adults [1113] although not all studies confirmed this association [14]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, polyunsaturated fatty acids (PUFA) and their metabolites, the long-chain PUFA (LC PUFA) such as eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) of the n-3 series and arachidonic acid (ARA, 20:4n-6) of the n-6 series have been linked to BP [11, 12, 14]. As precursors for the production of prostaglandins and thromboxanes with effects on vasodilation and platelet aggregation LC PUFA can affect BP [15].…”
Section: Introductionmentioning
confidence: 99%